Subcutaneous implantation after endoscopic and traditional thyroid surgery: a retrospective case report - Zhang, Tingting; Ni, Zhaoxian; Ma, Ben; Ji, Qinghai; Qu, Ning; Shi, Rongliang; Wang, Yu (Frontiers in Oncology, 2024)
Subcutaneous implantation is an unexpected complication of thyroid surgery. Our study aimed to analyze the clinical features and outcomes of implantation after thyroid surgery. We retrospectively searched for the patients with implants of thyroid tumor after surgery from our database prior to August 2023. The clinical and pathological data were reviewed. Six female patients with an mean age of 33.6±13.3 years were enrolled in this study. There was a rare case with mucinous adenocarcinoma, three follicular thyroid carcinoma and two papillary thyroid carcinoma. The case with primary enteric adenocarcinoma of thyroid with subcutaneous implantation was firstly reported. The patient with mucinous adenocarcinoma received six courses of TP regimen chemotherapy. Five cases received radioactive iodine therapy. After a mean of 69.5 months follow-up, one case recurred in the lateral region and no metastasis or recurrence happened in the other 5 cases. Although the implantation after thyroid surgery is uncommon, the cases serve as a reminder to take greater care to avoid implantation.